2006
DOI: 10.1097/00001665-200605000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Ostene, a New Water-Soluble Bone Hemostasis Agent

Abstract: Traditional formulations of bone wax are composed largely of beeswax and are well known to interfere with bone healing and cause inflammatory reactions. Ostene, a newly available bone hemostasis agent made of water-soluble alkylene oxide copolymers, was evaluated. The soft tissue response to Ostene was compared with bone wax and a polyethylene control after implantation into the paravertebral muscles of three rabbits. After 2 weeks, Ostene elicited no fibrous response, the polyethylene elicited a thin (less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 34 publications
1
56
0
Order By: Relevance
“…11) Many different materials, such as calcium phosphate cement, absorbable microfibrillation collagen, fibrins and dissoluble alkylene oxide copolymers were used instead of bone wax to control the bleeding on sternal sides, and their properties were compared with bone wax. [12][13][14] In our study, any statistically significant difference was not found between groups considering the quantity of bleeding, amount of blood and blood products used and deep sternal infection. It could not be shown that the application of bone wax significantly reduces bleeding following sternotomy.…”
Section: Discussionmentioning
confidence: 70%
“…11) Many different materials, such as calcium phosphate cement, absorbable microfibrillation collagen, fibrins and dissoluble alkylene oxide copolymers were used instead of bone wax to control the bleeding on sternal sides, and their properties were compared with bone wax. [12][13][14] In our study, any statistically significant difference was not found between groups considering the quantity of bleeding, amount of blood and blood products used and deep sternal infection. It could not be shown that the application of bone wax significantly reduces bleeding following sternotomy.…”
Section: Discussionmentioning
confidence: 70%
“…Once applied to bone, bone wax remains at the site indefinitely. Bone wax is known to interfere with bone healing, elicit chronic inflammatory reactions, and increase infection rates (Allison, 1994;Chun, 1988;Finn, 1992;Johnson, 1981;Nelson, 1990;Gibbs, 2004;Sawan et al, 2010;Wellisz et al, 2006Wellisz et al, , 2008aWellisz et al, , 2008b. 7 And yet, the use of bone wax remains relatively widespread, and surgeons are often unaware of the complications surrounding its application.…”
Section: Effective Bone Hemostasismentioning
confidence: 99%
“…Once applied to the bone, the material remains at the surgical site indefinitely. It may become a nidus of infection and if contaminated, it may cause infection of the soft tissue or osteomyelitis (Allison, 1994;Chun et al, 1988;Finn et al, 1992;Gibbs et al, 2004;Johnson et al, 1981;Nelson et al, 1990;Wellisz et al, 2006Wellisz et al, , 2008aWellisz et al, , 2008b.…”
Section: Bone Wax As Bone Hemostasis Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional bone wax is chiefly composed of beeswax but this material sometimes interferes with bone healing by causing an inflammatory reaction. 1) Moreover, the beeswax has some possibility of causing infection, because it derives from animals. Thus novel materials are needed in order to avoid such infection and to promote bone healing without causing an inflammatory reaction.…”
Section: Introductionmentioning
confidence: 99%